2019
DOI: 10.1142/s1363919619500294
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Innovation Implementation and Speed to Market on the Relationship Between Team Sense-Making, Trust, and NPD Success

Abstract: New product development (NPD) has long been regarded as an important issue for the success of business operations. One of the key determinants of NPD is innovation, which is highly related to innovation implementation. Both innovation implementation and NPD success require team sensemaking and trust. The purpose of this study is to examine the antecedents of innovation implementation and its mediating role through which it influences NPD success. A causal model was developed to examine relevant variables for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Design practices, quality management techniques such as lean and Six Sigma and lack of strategic vision are the significant challenges in promoting effective NPD. The implementation of innovative practices and NPD success requires team sense-making and trust (Amaya et al , 2019). The high level of trust in the information technology and the use of organizational innovations for the execution of strategic intent in the high-tech firms compensate for the lack of clarity on the information technology strategies adopted by the firms (Ettlie et al , 2017).…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…Design practices, quality management techniques such as lean and Six Sigma and lack of strategic vision are the significant challenges in promoting effective NPD. The implementation of innovative practices and NPD success requires team sense-making and trust (Amaya et al , 2019). The high level of trust in the information technology and the use of organizational innovations for the execution of strategic intent in the high-tech firms compensate for the lack of clarity on the information technology strategies adopted by the firms (Ettlie et al , 2017).…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…Estimates exist that about half of all innovations fail to provide the expected benefits to the adopting organization (Aiman-Smith and Green, 2002;Repenning, 2002). This is not caused by the ineffectiveness of the innovation itself, but by an ineffective implementation process (Klein and Knight, 2005;Amaya et al, 2018). Many studies on innovation consider innovation adoption as the end of the innovation process, overlooking that innovations do not create a competitive advantage unless they are effectively implemented (McGrath et al, 1996).…”
Section: Problem Statement and Research Questionsmentioning
confidence: 99%
“…Innovation research has identified several reasons for why an effective innovation implementation is challenging for organizations, e.g. the need to develop additional skills to use the innovation (Aiman-Smith and Green, 2002), the required change of roles and routines in the company (Adolfsson et al, 2004;Amaya et al, 2018), and the high financial and temporal expenditures associated with the innovation (Repenning, 2002). Though these challenges of innovation implementation are well known, nowadays companies face additional problems, e.g.…”
Section: Challenges and Related Work Challenge 1: Effective Innovation Implementationmentioning
confidence: 99%
“…Amaya et al introduced team sense-making capability and trust as critical sources of innovation implementation and success (17). Trust and sense-making allow teams to fast-track introduction of new processes or approaches by gathering new information to generate knowledge about opportunities or technology.…”
Section: Introductionmentioning
confidence: 99%